The newspaper widow - Brainard, Cecilia Manguerra (Manila University of Santo Tomas Publishing House, 2017)
"Ines Maceda, the "newspaper widow," aims to clear her son's name. He has been accused of murdering a priest. In addition, Ines grieves for her deceased husband and combats the lingering trauma of earlier miscarriages. Her development is one of the shining elements of the novel-she feels tangible, rooted in the story and the setting. The Newspaper Widow offers a nuanced glance into Filipino society circa 1908. It is a world rich with history, myth, and ritual; descriptions pulse with life, providing crucial insights into aspects of Filipino culture and world colonial history, such as encounters with the "Island of the Living Dead," sectioned off to contain those inflicted with leprosy, and once the world's largest leper colony. " - From a review by Mya Alexice
"The newspaper widow was first published by the University of Santo Tomas Publishing House, copyright ©2017, Cecilia Manguerra Brainard"--Title page verso.
Novel.
In English.
Keywords: Philippine fiction (English)